ANALISIS PENGARUH LEVERAGE, PROFITABILITAS, DAN UKURAN PERUSAHAAN TERHADAP KUALITAS PELAPORAN KEUANGAN (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2015-2019) - Muhammad Azka Aulawy; Dwi Cahyo Utomo (Diponegoro Journal of Accounting, 2021)
The purpose of this study is to analyze the influence of leverage, profitability, and firm size on the financial reporting quality in manufacturing companies listed on the Indonesian Stock Exchange during five-year study period (2015-2019). The population of this study is 169 manufacturing companies. Determination of the sample using purposive sampling method so that the sample used in this study was 34 manufacturing companies. The research data were obtained from the annual financial reports of manufacturing companies which were sourced from the respective companies' websites and the Indonesia Stock Exchange website. The statistical tools used include factor analysis, descriptive statistics, classical assumption test, and multiple linear regression. The results of this study indicate that firm size has a significant positive effect on the financial reporting quality, while leverage and profitability are not statistically significant in affecting the financial reporting quality.